Accounting Ethics in Financial Reporting in The Context of The Metaphor of ‘Lawang Sewu’ (thousands of doors, thousands of information, thousands of interests) - Debi Setyawati; Erina Sudaryati (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to improve the readability and understanding of financial statements through a conceptual framework of financial reporting and its derivatives. This study employed an analytical method as a conceptual framework, where financial accounting standards, financial reporting, and the results are described by the term